The anxious achiever : turn your biggest fears into your leadership superpower - Aarons-Mele, Morra (Ascent Audio, 2023)
Anxiety disorders are the most common mental illnesses in the world. But in our workplaces, anxiety has been a hidden problem-there in plain sight but ignored. Until now. The Anxious Achiever is a book with a mission: to normalize anxiety and leadership. As leadership expert and self-proclaimed anxious achiever Morra Aarons-Mele argues, anxiety is built into the very nature of leadership. It can-and should-be harnessed into a force for good. Inspired by the popular podcast of the same name, The Anxious Achiever is filled with personal stories, research-based insights into mental health, and lots of practical advice. You'll learn how to: figure out your own anxiety profile so that you can recognize and avoid common thought traps and triggers; confront bad habits and unhealthy coping mechanisms; resist perfectionism, manage social anxiety, and set boundaries to prevent burnout; deal with feedback, criticism, and impostor syndrome; and model-and communicate-healthy behavior as a leader. Whether you're experiencing anxiety for the first time or have been battling it for years, The Anxious Achiever will help you turn your stress and worries into a source of strength for yourself, your career, and the people you lead.